Functional carbon-based coating for thermal management in smart windows - Kiw, Si Yang (2019)
Smart window technologies have been widely researched on for the past few years with the aim of reducing energy consumption through thermal energy, especially from both commercial and residential buildings. Many of the current technologies do not tackle the heat transfer via radiation and conduction. Furthermore, large scale production of the current innovative materials can give rise to increasing costs. In this study, a facile and cost-effective method is introduced to overcome these setbacks. The aim of this study is to achieve the heat modulation while not compromising the transparency of the glass window by coating a composite thin film that consists of a combination of Graphene derivative called Graphene Quantum Dots (GQDs) and a highly transparent polymer called Polyvinylpyrrolidone (PVP). The thin film samples were characterised using Transmission electron microscopy (TEM), X-Ray Diffraction (XRD), Atomic Force Microscopy (AFM), Fourier-transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS), Fluorescence Spectroscopy, and thermal diffusivity. Results show that the GQDs-PVP composite thin films possess excellent optical property of GQDs (with more than 80% of visible transparency). In addition, the GQD-PVP composite thin films demonstrate a reduction in thermal diffusivity through FTO glass substrate (from 0.55 mm2/s to zero within a period of 4 s). Hence, the low cost and eco-friendly GQDs-PVP composite thin films are expected to be a promising material for heat management in smart window applications.